Motion System of a Four-Wheeled Robot Using a PID Controller Based on MPU and Rotary Encoder Sensors - Sagita, Muhamad Rian; Ma’arif, Alfian; Furizal, Furizal; Rekik, Chokri; Caesarendra, Wahyu; Majdoubi, Rania (Control Systems and Optimization Letters, 2024)
This research addresses the challenge of developing an effective motion system for a four-wheeled omnidirectional robot configured with wheels at a 45-degree angle, allowing for holonomic movement—motion in any direction without changing orientation. In this system, inverse kinematics calculates each wheel's angular velocity to optimize movement. PID control is implemented to stabilize motor speeds, while odometry guides and determines the robot’s position using initial and target coordinates. The robot operates on a 12-volt power supply and two STM32F103C microcontrollers, utilizing an MPU6050 sensor to maintain orientation and optical rotary encoders for accurate positional tracking. Experimental results demonstrate that the robot achieves optimal motion on x and y axes with PID settings of kP = 0.8, kI = 1.0, and kD = 0.08. This configuration yields a rise time of 0.95 seconds, overshoot of 7.36%, and steady-state error of -0.5 RPM at a setpoint of 350 RPM. Using odometry, the robot successfully navigates various movement patterns with average position errors of 1.2% on the x-axis and 1.6% on the y-axis for rectangular patterns, 2.1% on the x-axis and 2.2% on the y-axis for zig-zag patterns, and 1.75% on the x-axis and 1.15% on the y-axis for triangular patterns. The MPU6050 sensor maintains orientation with an error of 0.65% in triangular patterns and 0.85% in rectangular patterns. Through inverse kinematics, PID control, and sensor integration, the robot reliably follows designated coordinate points.